2017
DOI: 10.4306/pi.2017.14.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Mood Status and Psychosocial Well-Being with Depression During Interferon-Based Treatment for Hepatitis C

Abstract: ObjectiveThe aims of this prospective study were to investigate temporal changes in mood status and distress level, as well as the development of depression, during pegylated interferon (PEG-IFN)-based treatment of patients with chronic hepatitis C (CHC). We also explored whether baseline demographic, psychiatric, and personality traits predicted the evolution of depression.MethodsCHC patients without depression were screened with laboratory tests; psychiatric interviews; and evaluations of mood symptoms, leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The peak of somatic pain scores at 8th week may imply the cumulative result of stress response to chronic pain and contributed to the higher incidence of depressive episodes in the first 8 weeks of our study. Similarly, previous literature also reported a higher depression incidence in the first 8 weeks in HCV patients receiving IFN-α therapy ( Choi et al., 2017 ; Horikawa et al., 2003 ; Malaguarnera et al., 2001 ). Moreover, previous literature revealed a positive predictive effect of somatic pain, especially non-specific musculoskeletal complaints, on the occurrence of depression ( Gerber et al., 1992 ).…”
Section: Discussionsupporting
confidence: 68%
“…The peak of somatic pain scores at 8th week may imply the cumulative result of stress response to chronic pain and contributed to the higher incidence of depressive episodes in the first 8 weeks of our study. Similarly, previous literature also reported a higher depression incidence in the first 8 weeks in HCV patients receiving IFN-α therapy ( Choi et al., 2017 ; Horikawa et al., 2003 ; Malaguarnera et al., 2001 ). Moreover, previous literature revealed a positive predictive effect of somatic pain, especially non-specific musculoskeletal complaints, on the occurrence of depression ( Gerber et al., 1992 ).…”
Section: Discussionsupporting
confidence: 68%
“…Also, some patients suffering from chronic inflammatory diseases (e.g., cardiovascular diseases) had a higher incidence rate of depression ( 8 ). In addition, 50% of the hepatitis C patients receiving interferon-α (IFN-α, a pro-inflammatory cytokine) treatment had depressive symptoms ( 9 , 10 ). Our previous studies also suggested that both chronic mild stress in rats and the administration of lipopolysaccharides (LPS) in mice induced an increase in pro-inflammatory cytokines in the prefrontal cortex and hippocampus as well as depressive-like behaviors ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is quite common in other studies on depression in which the initial severity of depressive symptoms was a strong predictor of depressive symptomatology. [23][24][25][26] Depressive symptoms in general seem to be the main predictor of depressive disorders and broad psychiatric and somatic symptomatology. A similar situation has been replicated in the present study -depressive symptoms, despite their origin, foreshadowed MDD in patients treated for hepatitis C. Moreover, the diagnosis of depression during treatment depended solely on the initial severity of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%